China’s Asymmetric Warfare in Indonesia: The Case of Turnkey Project Management - Fitria Fitria (Cenderawasih University, 2021)
This article aims to shed light on China’s asymmetric warfare in Indonesia through the Turnkey Project Management (TPM) scheme. TPM is an employment contract to carry out Chinese investment with a one-package system starting from funding with the preferential buyer’s credit system, materials and machines, experts, and workers, are emanated from China. This study employed qualitative research and used a research library to collect data. It found that TPM is an integral part of China’s foreign policy to pursue its national interests. China also relies more on its state-owned enterprises and private companies (non-state actors), thereby minimizing the state’s role. Indonesia suffered from losses more than it gains from the win, implying this scenario is more of a zero-sum game. The foreign workers from China have also caused social problems in Indonesia, such as cybercrime and the smuggling of methamphetamine. The results of this study include recommendations for enabling Indonesian workers to adapt to foreign technology regarding a transfer of knowledge; strengthening regulations that meet environmental standards, human rights, and good corporate governance in terms of foreign investment; and not to make the regulation easier for allowing Chinese workers. KEYWORDS Asymmetric Warfare; China; Indonesia; Turnkey